2013
DOI: 10.1371/journal.pone.0085160
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Microenvironments and Copper Binding Alters the Conformation and Toxicity of a Prion Fragment

Abstract: The secondary structures of amyloidogenic proteins are largely influenced by various intra and extra cellular microenvironments and metal ions that govern cytotoxicity. The secondary structure of a prion fragment, PrP(111-126), was determined using circular dichroism (CD) spectroscopy in various microenvironments. The conformational preferences of the prion peptide fragment were examined by changing solvent conditions and pH, and by introducing external stress (sonication). These physical and chemical environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…We also found that Zn 2+ and Cu 2+ significantly inhibited PrP106–126 oligomerization using the thioflavin T (ThT) fluorescence assay, far-ultraviolet circular dichroism (CD) spectroscopy, and atomic force microscopy (AFM) imaging. Although Cu 2+ and Zn 2+ reportedly facilitate the aggregation of AβP [ 91 ], our results coincide with other studies, which indicate that PrP-induced conformational changes and toxicity are attenuated by Cu [ 92 , 93 ]. Moreover, Cu 2+ reportedly inhibits the aggregation of human islet amyloid peptide (amylin) [ 94 ], Thus, it is highly possible that Cu 2+ exhibits complex effects on the oligomerization of amyloidogenic proteins.…”
Section: Toxic Functions Of Prp and Neurometalssupporting
confidence: 91%
“…We also found that Zn 2+ and Cu 2+ significantly inhibited PrP106–126 oligomerization using the thioflavin T (ThT) fluorescence assay, far-ultraviolet circular dichroism (CD) spectroscopy, and atomic force microscopy (AFM) imaging. Although Cu 2+ and Zn 2+ reportedly facilitate the aggregation of AβP [ 91 ], our results coincide with other studies, which indicate that PrP-induced conformational changes and toxicity are attenuated by Cu [ 92 , 93 ]. Moreover, Cu 2+ reportedly inhibits the aggregation of human islet amyloid peptide (amylin) [ 94 ], Thus, it is highly possible that Cu 2+ exhibits complex effects on the oligomerization of amyloidogenic proteins.…”
Section: Toxic Functions Of Prp and Neurometalssupporting
confidence: 91%
“…Solution conditions previously have been found to have significant effects on peptide conformations. For example, the prion protein, PrP has been found to adopt different conformations, specifically with respect to the proportions of α-helical and β-sheet structures, in aqueous solutions, in surfactant solutions, and following sonication . Similarly, secondary structure and aggregation of Aβ peptides has been found to be influenced by solvent conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the prion protein, PrP has been found to adopt different conformations, specifically with respect to the proportions of α-helical and β-sheet structures, in aqueous solutions, in surfactant solutions, and following sonication. 109 Similarly, secondary structure and aggregation of Aβ peptides has been found to be influenced by solvent conditions. In early studies by Shen and Murphy, Aβ(1−39) was not found to have any detectable β-sheet content in neat dimethyl sulfoxide (DMSO); however, in 0.1% trifluoroacetate the peptide contained approximately 1 / 3 β-sheet, and approximately 2 / 3 β-sheet in 35% acetonitrile/0.1% trifluoroacetate, which is thought to be most similar to the fibrillar form of the peptide under physiological conditions.…”
Section: Effect Of Solution Conditions On Cu(ii)mentioning
confidence: 99%
“…39 It is well known that the hydrophobic 112-125 region of hPrP undergoes random coil to α-helix transition in the presence of membrane like environments (surfactant or lipid micelles) and structuring solvents. [43][44][45][46][47] Similarly to what happens to other amyloidogenic proteins, like Aβ and αS, this structural rearrangement strongly impacts Cu 2+ binding modes in terms of both donor atoms and affinity. 47,48 As we recently demonstrated, the interaction of hPrP91-127 with anionic micelles facilitates simultaneous copper coordination to both His96 and His111, which on the other hand behaves as separate metal anchoring sites in the absence of micelle environment.…”
Section: Introductionmentioning
confidence: 97%